Self-assembly of gelatin and collagen in the polyvinyl alcohol substrate and its influence on cell adhesion, proliferation, shape, spreading and differentiation - Wu, I-Chi; Liou, Je-Wen; Yang, Chin-Hao; Chen, Jia-Hui; Chen, Kuan-Yu; Hung, Chih-Huang (Frontiers in Bioengineering and Biotechnology, 2023)
Culture substrates display profound influence on biological and developmental characteristic of cells cultured in vitro. This study investigates the influence of polyvinyl alcohol (PVA) substrates blended with different concentration of collagen or/and gelatin on the cell adhesion, proliferation, shape, spreading and differentiation of stem cells. The collagen/gelatin blended PVA substrates were prepared by air drying. During drying, blended collagen or/and gelatin can self-assemble into macro-scale nucleated particles or branched fibrils in the PVA substrates that can be observed under the optical microscope. These collagen/gelatin blended substrates revealed different surface topography, z-average, roughness, surface adhesion and Young's modulus as examined by the atomic force microscope (AFM). The results of Fourier transform infrared spectroscopy (FTIR) analysis indicated that the absorption of amide I (1600-1700 cm-1) and amide II (1500-1600 cm-1) groups increased with increasing collagen and gelatin concentration blended and the potential of fibril formation. These collagen or/and gelatin blended PVA substrates showed enhanced NIH-3T3 fibroblast adhesion as comparing with the pure PVA, control tissue culture polystyrene, conventional collagen-coated and gelatin-coated wells. These highly adhesive PVA substrates also exhibit inhibited cell spreading and proliferation. It is also found that the shape of NIH-3T3 fibroblasts can 3 be switched between oval, spindle and flattened shapes depending on the concentration of collagen or/and gelatin blended. For inductive differentiation of stem cells, it is found that number and ration of neural differentiation of rat cerebral cortical neural stem cells increase with the decreasing collagen concentration in the collagen-blended PVA substrates. Moreover, the PVA substrates blended with collagen or collagen and gelatin an efficiently support and conduct human pluripotent stem cells to differentiate into Oil-Red-O-and UCP-1-positive brown-adipocyte-like cells via ectodermal lineage without the addition of mitogenic factors. These results provide a useful and alternative platform for controlling cell behavior in vitro and may be helpful for future application in the field of regenerative medicine and tissue engineering.